1984
DOI: 10.3109/10826088409057176
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Care Program for Pregnant Addicts: Obstetrical, Neonatal, and Child Development Outcomes

Abstract: This study reports the results of a comprehensive care program for pregnant addicts, one that provides medical, counseling, and child development services. Findings include the following. Women who enroll while pregnant generally stay through childbirth, and most deliveries are free of complication. Most newborns are of normal gestational age and birthweight, and these outcomes are directly related to length and amount of prenatal care. Neonatal withdrawal is directly related to prenatal maternal methadone dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
2

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 18 publications
1
31
1
2
Order By: Relevance
“…Our study confirms the high incidence of preterm deliveries (table IV) as reported in opiate addicts [1,3,18,19,23] which may be due to drug withdrawal attacks [25]. However, only one of our infants was less than 33 weeks of gestation.…”
Section: Prematuritysupporting
confidence: 94%
See 2 more Smart Citations
“…Our study confirms the high incidence of preterm deliveries (table IV) as reported in opiate addicts [1,3,18,19,23] which may be due to drug withdrawal attacks [25]. However, only one of our infants was less than 33 weeks of gestation.…”
Section: Prematuritysupporting
confidence: 94%
“…The rising heroin abuse in North America in the sixties prompted comprehensive reports of neonatal opiate withdrawal [19,23,26,28]. In Europe, neonatal heroin addiction has become a problem within the last 20 years [1,3,18] demanding for professional and standardized prenatal and neonatal care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the results of a retrospective case control study comparing methadone-maintained pregnant subjects with untreated women showed that both groups used illicit substances at high rates and gave birth to infants of similar weight, although the treated women had more prenatal care (Edelin, Gurganious, Golar, Oellerich, Kyei-Aboagye, & Hamid, 1988). Conversely, Suffet and Brotman (1984) have reported that a comprehensive care program for pregnant opiate-dependent women, including medical, counseling, and child development services, resulted in improved pregnancy outcome. However, no data from a comparison group were presented.…”
Section: Introductionmentioning
confidence: 99%
“…An early study by Chang and colleagues 51 showed that enhanced prenatal care and comprehensive services have better results than a traditional methadone program despite equivalent dose ranges for maintenance. 51,52 There is also some debate about whether higher or lower doses at delivery are of particular benefit. Lower doses are associated with less neonatal withdrawal, but higher doses during the pregnancy and at delivery are associated with better patient compliance, reduced relapse risk, and higher neonatal birthweights.…”
Section: What Is the Epidemiology Of Opioid Use During Pregnancy Andmentioning
confidence: 99%